Knowledge and practice among the pediatric post graduate residents regarding the technique of blood culture sampling - Inamdar, Nusrat R.; Wade, Minal R.; Mauskar, Anupama (International Journal of Research in Medical Sciences, 2019)
Background: Errors in sampling during blood culture, may lead to contaminants or poor yield which result in faulty reports increasing patient's suffering, endanger patient safety and increasing cost of health care. Optimal knowledge about the sampling method for important microbiological test like blood culture translates into appropriate practices. Authors objectives was to assess the knowledge and practice of the Pediatric resident doctors, regarding sterile technique during blood culture collection. The change in the knowledge of the residents during blood culture sampling with regards to maintaining asepsis after watching educational video was evaluated. Methods: A quasi experimental, questionnaire based study with pre–post intervention, involved post graduate resident’s knowledge and practice regarding the sterile technique during blood culture collection. The data analyzed using paired t test and Chi-square Test. Results: 18(60%) participants accepted that they have collected blood culture not maintaining complete asepsis at some time in past. The reasons for the same were lack of knowledge 14 (46.66%), no assistance from staff for the procedure 14 (46.66%), non-availability of sterile gloves 4 (13.33%), non-availability of antiseptic solution 4(13.33%), time consuming 8 (26.66%). Conclusions: Ultimately, blood culture contamination is a complex, challenging problem that requires a multidisciplinary approach. Regular teaching modules for the health personnel and ensuring environment conducive to correct practises would definitely help in improving the sampling practises for aseptic procedures.